ANALISIS TINGKAT KEPUASAN DAN LOYALITAS KONSUMEN PADA KEDAI KOPI DI KECAMATAN KUTA ALAM KOTA BANDA ACEH - Siva Safira; Cut Faradilla; Indra Indra (Jurnal Agrisep, 2021)
This study aims to determine the level of consumer satisfaction in consuming products at a coffee shop in Kuta Alam District. The type of data used in this study is primary data, namely data obtained from the first party who is directly involved with the problem to be discussed. Primary data obtained through interviews with coffee shop consumers. The analytical model used is the Customer Satisfaction Index (CSI). The results in this study are the CSI value obtained, which is 81% that included in the very satisfied criteria. This shows that the performance of the coffee shop is in line with consumer expectations. So, based on the calculation of the Customer Satisfaction Index (CSI) the level of consumer satisfaction of the coffee shop in Kuta Alam District is at a very satisfied level.